Amoxicillin Induced Behavioral Neurotoxicity and Histopathological Changes in Organs of Albino Rats - Paudel, Sabita; Aryal, Bijay; Ranabhat, Sunita (Journal of College of Medical Sciences-Nepal, 2020)
Background: There are various adverse drug reactions of penicillin. Neurotoxicity is attracting the attention of researchers all over the world. It also affects other organs like liver, kidney, heart and testes Methods: The study was conducted at pharmacy and pharmacology department of Gandaki Medical College (GMC) from January till April, 2018. Albino rats were divided six each in test and control group. Tests were administered amoxicillin 90mg/kg/d and control with distilled water for 10 days. After 10 days, rats were tested for neurotoxicity with rota-rod (RR) and modified forced swim test (MFST). They were then sacrificed under anesthesia, organs were dissected and sent for histopathological investigation. Results: The latency to fall from RR apparatus decreased significantly in test rats than control. (P value = 0.0001) In MFST, immobility time was significantly increased than control (P value = 0.0001). Swimming time(ST) was significantly decreased (P value = 0.001) and climbing time (CT) was not significantly altered in test rats than control (P value = 0.352). The liver enzyme, AST and ALT were significantly increased in the test rats (TR) as compared to controls. (P value 0.049 and 0.001 respectively) Brain of test rats (TR) showed shrunken neurons surrounded by perineuronal vacuolations, liver and kidney showed degenerative changes. Vacuolations and pyknotic cells were seen in spermatogonic cells. Conclusions: Neurotoxic effects were seen in test rats which recommends regulation of the administration of high dose of penicillin.